Q. 75.0( 2 Votes )

If P (A)=6/11,P (

Answer :

We have, P (A B) = P (A)+ P (B)- P (A B)

i. From above formula,

P (A B)= P (A)+ P (B) - P (A B)


= (answer)

ii. =


iii. = = (answer)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

State True or FalMathematics - Exemplar

Fill in theMathematics - Exemplar

A speaks truth inMathematics - Board Papers

Often it is takenMathematics - Board Papers

Assume that each Mathematics - Board Papers

A bag X contains Mathematics - Board Papers